Impacts of surface water interchange between urban rivers and fish ponds in Chu river of Nanjing, China: A potential cause of greenhouse gas emissions - Liu, Yi-Xuan; Abdela, Kemal Adem; Tang, Zhen-Ni; Yu, Jie-Yu; Zhou, Xu-Dong; Kumar, Amit; Yu, Zhi-Guo (Frontiers in Environmental Science, 2022)
Surface water interchange between aquaculture ponds and urban rivers is commonly used for the abatement of water pollution and regulating ecological services. Although, underlying impact of surface water interchange for greenhouse gas (GHG) emissions is yet to be explored. In this study, sediment microcosm incubation and field observation has been employed to understand the impact of surface water interchange on GHG potential over aquaculture ponds and urban rivers, and further characterize their underlying mechanism. Results showed that Fish pondinterchange (Pint) and Chu River riparian (CRR) exhibit a similar variation pattern of GHG emission rate. Consequently, annual accumulative emissions of methane, carbon dioxide, and nitrous oxide of CRR were 0.89, 2.1, and 20.83 folds than that of Pint, respectively. For the incubation experiment, primarily it was assessed that fish-pond-overlying water treatments had larger accumulative GHG emissions than deionized water treatments, which is in agreement with the field observation. Secondly, the process of surface water interchange altered the concentrations of nutrients in benthic sediment from both sites of CRR and Pint, thereby increased the GHG accumulative in the CRR and showing reciprocate results in case of Pint. This study could be helpful to reduce the potential GHG emissions from urban freshwater bodies in the future by adopting strategic mitigation measures like catchment area treatment plans in the vicinity of urban river catchment.